FENOMENA PERLUASAN MAKNA PADA IKLAN PRODUK LION WINGS DAN RENCANA PELAKSANAAN PEMBELAJARANNYA DI SMA KELAS XII - Hesti Sulistyowati; Umi Faizah; Joko Purwanto (Pendidikan Bahasa dan Sastra Indonesia, 2022)
Abstract: This study aims to describe (1) the expansion of meaning in Lion Wings product advertisements; (2) the plan for the implementation of learning in SMA class XII. The data collection of this research was carried out by listening techniques, observation techniques, and documentation techniques. The data analysis technique used content analysis techniques. The results of data analysis are presented with informal techniques. From the results of this study, it was concluded that in the Lion Wings product advertisement there were (1) expansion of meaning found as many as 4 data; (2) the implementation plan of learning with advertising text material in class XII SMA is carried out using the 2013 curriculum with KD 3.1 Understanding the structure and rules of advertising texts, both verbally and in writing and 4.1 Interpreting the meaning of advertising texts, both orally and in writing. Learning is carried out with a scientific-based discovery learning model.Keywords: meaning expansion, Lion Wings product advertisement, and learning implementation plan.